Revolutionising pharmacy through machine learning: the progress and perils / Yuslina Zakaria - Zakaria, Yuslina (Faculty of Pharmacy, 2024)
Machine learning (ML) is transforming pharmacy, enhancing accuracy in drug discovery, personalised medicine, and patient care. ML, a branch of artificial intelligence (AI), uses algorithms such as neural networks, decision trees, and support vector machines to learn from large datasets and make predictions. In pharmaceutical research, ML accelerates the identification of potential drug candidates, improves design optimisation, and increases research efficiency. Additionally, ML in predictive analytics for pharmacy practice shows promising results, highlighting the need for further research and adoption to improve patient care (1).